2018
DOI: 10.1002/jmv.25005
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus detection in patients with acute gastroenteritis in Switzerland

Abstract: Acute gastroenteritis (GE) has a major impact on morbidity and mortality worldwide, yet comprehensive data regarding infectious agents including enteroviruses are scarce. We hypothesized that enteroviruses constitute a significant cause of acute GE. We analyzed 677 stool samples from 504 patients, which had been submitted for suspected infectious GE. 0.2 mL of stool suspension was extracted using the Abbott m2000 robot and analysed by multiplex nucleic acid testing (NAT) using the Luminex xTAG gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
4
7
1
Order By: Relevance
“…While most epidemiological studies on enteric viruses in children identified rotavirus as the first viral cause of acute sporadic gastroenteritis [24,25,26,27,28], we found a higher positivity rate for adenovirus, which could be biased on the fact that positive samples for rotavirus and adenovirus by immunochromatography were excluded from the analyses. Yet, two other recent studies also identified higher prevalence of adenovirus than rotavirus infection among a cohort of children with gastroenteritis using real-time PCR assays [29,30], including one study that focused on the post rotavirus vaccine era [30].…”
Section: Discussioncontrasting
confidence: 68%
“…While most epidemiological studies on enteric viruses in children identified rotavirus as the first viral cause of acute sporadic gastroenteritis [24,25,26,27,28], we found a higher positivity rate for adenovirus, which could be biased on the fact that positive samples for rotavirus and adenovirus by immunochromatography were excluded from the analyses. Yet, two other recent studies also identified higher prevalence of adenovirus than rotavirus infection among a cohort of children with gastroenteritis using real-time PCR assays [29,30], including one study that focused on the post rotavirus vaccine era [30].…”
Section: Discussioncontrasting
confidence: 68%
“…The reported incidence of bacterial gastroenteritis caused by less prevalent pathogens including Salmonella, STEC and L. monocytogenes were 14.7, 8.4 and 0.67 per 100,000 population in 2020, respectively (European Food Safety Authority, 2021b). A study by Gosert et al examined the detection of viral and bacterial pathogens from 677 stool samples collected from 504 patients with acute gastroenteritis between 2013 and 2015, and found that rotavirus (126/677), norovirus (82/677) and enterovirus (36/677) were the most prevalent viral pathogens, whilst Clostridium difficile(39/ 677) and Campylobacter(16/677) were the most prevalent bacterial pathogens (Gosert et al, 2018).…”
Section: Switzerlandmentioning
confidence: 99%
“…A study by Gosert et al. examined the detection of viral and bacterial pathogens from 677 stool samples collected from 504 patients with acute gastroenteritis between 2013 and 2015, and found that rotavirus (126/677), norovirus (82/677) and enterovirus (36/677) were the most prevalent viral pathogens, whilst Clostridium difficile (39/677) and Campylobacter (16/677) were the most prevalent bacterial pathogens ( Gosert et al., 2018 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…[ 1 2 ] They include rotavirus, norovirus, astrovirus, sapovirus, enteric adenovirus, parechovirus, enterovirus as well as other typically nonenteric infections that may manifest as diarrhea and vomiting such as influenza and coronaviruses. [ 3 4 5 6 7 8 ]Enteric viruses are also detected as part of co-infections, for which clinical significance has not been determined. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%